2012
DOI: 10.1016/j.ijhydene.2011.10.108
|View full text |Cite
|
Sign up to set email alerts
|

Wind park reliable energy production based on a hydrogen compensation system. Part II: Economic study

Abstract: Power production from renewable energy resources is increasing day by day. In the case of Spain, in 2009 it represented 26.9% of installed power and 20.1% of energy production. Wind energy makes the most important contribution to this production. Wind generators are greatly affected by the restrictive operating rules of electricity markets because, as wind is naturally variable, wind generators may have serious difficulties in submitting accurate generation schedules on a day-ahead basis, and in complying with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…They found that hydrogen energy storage technology using wind energy would economically be viable. Sanchez et al [16] illustrated economic evaluation of wind park based on a hydrogen compensation system consists of combining wind energy production with a biomass gasification system and a hydrogen generation system based on these two sources. They concluded feasibility of implementing this system.…”
Section: Hydrogen Production From Wind Energymentioning
confidence: 99%
“…They found that hydrogen energy storage technology using wind energy would economically be viable. Sanchez et al [16] illustrated economic evaluation of wind park based on a hydrogen compensation system consists of combining wind energy production with a biomass gasification system and a hydrogen generation system based on these two sources. They concluded feasibility of implementing this system.…”
Section: Hydrogen Production From Wind Energymentioning
confidence: 99%
“…Moreover, a lot of studies have been published about hydrogen as an energetic vector using renewable energy sources. Simulation studies have demonstrated the technical and economic viability of the use of hydrogen in wind farm compensation combined with a biomass gasification plant [5], [6], or in stand-alone systems for residential areas [7], [8], [9] combining wind energy production with solar photovoltaic and hydrogen storage [10]. Experimental studies demonstrate that it is possible to use this kind of energy storage in the scale of kW for residential application [11], [12] or even in extreme environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…A nuclear power plant is retained in Ref. [8] and [9]; a biomass gasification one is selected by Sá nchez et al (2012) [10].…”
Section: Introductionmentioning
confidence: 99%